Aspergillus in endodontic infection near the maxillary sinus - Gomes,Cinthya Cristina (2015)
ABSTRACT INTRODUCTION: Diseases of the maxillary sinus have been associated with dental roots near the maxillary sinus that have undergone endodontic treatment. OBJECTIVE: To investigate the presence of filamentous fungi in patients with dental roots near the maxillary sinus who had apical periodontitis treated endodontically, and to alert practitioners that this could be a possible avenue of contamination of the sinus in patients who develop maxillary sinus infection. METHODS: Cross-sectional study in 60 palatal roots of the first maxillary molars near the maxillary sinus, that underwent endodontic treatment for apical periodontitis. After removal of the filling material, dentin shavings were collected and placed in test tubes containing Sabouraud dextrose agar and chloramphenicol. The phenotype was determined by macroscopic and microscopic examination of the colonies. For polymerase chain reaction, the primers ITS-5 and ITS-4 were used. The sequences obtained were compared with those deposited at GenBank using the Basic Local Alignment Search Tool program. RESULTS: Filamentous fungi were isolated from 6 of 60 canals (10%):Aspergillus niger (6.7%), Aspergillus versicolor (1.6%), and Aspergillus fumigatus(1.6%). CONCLUSION: Root canals near the maxillary sinus with endodontic treatment and apical periodontitis may exhibit positive cultures for filamentous fungi. Interested professionals should be alert, because these microorganisms have pathogenic characteristics that can cause disease of odontogenic origin in the maxillary sinus.